Approach for topology partitioning in parallel network simulation - WANG Xiao-feng; FANG Bin-xing; YUN Xiao-chun; ZHANG Hong-li (Tongxin xuebao)
To improve the usability and running efficiency of the parallel network simulation,an approach for topology partitioning based on load estimation was realized: first,the relative load values of nodes and links,estimated according to their core levels in the topology map,were treated as their weights;then,the simulation task was partitioned by the graph partitioning tool.Experiments showed that this partitioning method could improve the performance of simulation by 16.4% compared to the partitioning method with no weights.Simulation of worms based on the real topology gathered via network measurement proves that the partitioning method is suitable for real large-scale network topology and can be used to simulate large-scale network security incidents.